Placing Nichiren in the "Big Picture": Some Ongoing Issues in Scholarship - Stone, Jacqueline I. (Japanese journal of religious studies, 1999)
This article places Nichiren within the context of three larger scholarly issues: definitions of the new Buddhist movements of the Kamakura period; the reception of the Tendai discourse of original enlightenment (hongaku) among the new Buddhist movements; and new attempts, emerging in the medieval period, to locate 'Japan" in the cosmos and in history. It shows how Nichiren has been represented as either politically conservative or radical, marginal to the new Buddhism or its paradigmatic figure, depending upon which model of "Kamakura new Buddhism" is employed. It also shows how the question of Nichiren's appropriation of original enlightenment thought has been influenced by models of Kamakura Buddhism emphasizing the polarity between "old" and "new" institutions and suggests a different approach. Lastly, it surveys some aspects of Nichiren's thinking about "Japan" for the light they shed on larger, emergent medieval discourses of Japan's religiocosmic significance, an issue that cuts across the "old Buddhism"/"new Buddhism" divide.